2020
DOI: 10.21037/atm-20-5307
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota metabolite trimethylamine N-oxide in functional impairment of bone marrow mesenchymal stem cells in osteoporosis disease

Abstract: Background: Osteoporosis (OP) is a prevalent metabolic bone disease characterized by bone loss and structural deterioration, which increases the risk of fracture especially in older people. Recent research has shown that gut microbes play an important role in OP. Trimethylamine N-oxide (TMAO), a gut microbiotaderived metabolite, has been implicated in the pathogenesis of diseases, including Alzheimer's and cerebrovascular disease. This study aimed to examine the effect of TMAO in OP.Methods: In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 22 publications
0
35
2
Order By: Relevance
“…In recent decades, bone marrow mesenchymal stem cells (BMSCs) have emerged as potential microenvironmental modulators (6,7). BMSCs, as a type of non-hematopoietic multipotent stem cell, can be differentiated into various cell types, including osteoblasts, adipocytes, and chondrocytes, under specific conditions (8,9). An increasing number of studies have indicated that OP is mainly attributable to the imbalance between the osteogenesis and adipogenesis of BMSCs (10).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, bone marrow mesenchymal stem cells (BMSCs) have emerged as potential microenvironmental modulators (6,7). BMSCs, as a type of non-hematopoietic multipotent stem cell, can be differentiated into various cell types, including osteoblasts, adipocytes, and chondrocytes, under specific conditions (8,9). An increasing number of studies have indicated that OP is mainly attributable to the imbalance between the osteogenesis and adipogenesis of BMSCs (10).…”
Section: Introductionmentioning
confidence: 99%
“…The normal gut microbiota in the human body is mainly composed of firmicutes, Bacteroidetes, proteobacteria, and actinomycetes. According to the impact on human health, gut microbiota can be divided into three categories: symbiotic bacteria, opportunistic bacteria, and pathogenic bacteria, which are dynamically balanced to maintain the homeostasis of the intestinal environment (2). Intestinal beneficial bacteria (i.e., probiotics) include bifidobacteria, lactobacillus, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The TNF gene encodes a multifunctional proinflammatory cytokine involved in the regulation of various biological processes, including cell proliferation, differentiation, apoptosis, lipid metabolism, and blood coagulation. It has been proven that TMAO can promote the production of the proinflammatory cytokines IL-1 β , IL-6, and TNF- α in vitro [ 39 , 40 ], and the activation of the NF- κ B pathway is necessary for TMAO to induce bone marrow mesenchymal stem cells to produce proinflammatory cytokines and release active oxygen [ 40 ]. TNF was determined to be closely related to acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%